2017
DOI: 10.1039/c7nr02337e
|View full text |Cite
|
Sign up to set email alerts
|

Helix-sense-selective co-precipitation for preparing optically active helical polymer nanoparticles/graphene oxide hybrid nanocomposites

Abstract: Constructing optically active helical polymer based nanomaterials without using expensive and limited chirally helical polymers has become an extremely attractive research topic in both chemical and materials science. In this study, we prepared a series of optically active helical polymer nanoparticles/graphene oxide (OAHPNs/GO) hybrid nanocomposites through an unprecedented strategy-the co-precipitation of optically inactive helical polymers and chirally modified GO. This approach is named helix-sense-selecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
19
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

5
0

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 71 publications
2
19
1
Order By: Relevance
“…It is further indicative of that the polymer chains in P-1 and P-2 nanoparticles formed helical conformations but with left-and right-handed helices in equal amount, referring to our earlier series of studies dealing with helical poly acetylenes and the particles thereof. [7][8][9][10][11][12] The obtained P-3 and P-4 nanoparticles were also characterized by CD and UV-vis techniques and the obtained spectra are presented in Figure 3A,B. In Figure 3A, intense mirror-image CD signals are observed at about 300 nm, in which P-3 nanoparticles show the minus signal while P-4 nanoparticles show the plus signal.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is further indicative of that the polymer chains in P-1 and P-2 nanoparticles formed helical conformations but with left-and right-handed helices in equal amount, referring to our earlier series of studies dealing with helical poly acetylenes and the particles thereof. [7][8][9][10][11][12] The obtained P-3 and P-4 nanoparticles were also characterized by CD and UV-vis techniques and the obtained spectra are presented in Figure 3A,B. In Figure 3A, intense mirror-image CD signals are observed at about 300 nm, in which P-3 nanoparticles show the minus signal while P-4 nanoparticles show the plus signal.…”
Section: Introductionmentioning
confidence: 99%
“…That is, the formation of hydrogen bonds between achiral monomers and chiral additives is a key factor for the successful chiral induction in HSSDP, which is also found and discussed in detail in our previous studies dealing with helix-sense-selective polymerizations. [7][8][9][10][11][12] Besides, we also found that the prepared chiral P-2 nanoparticles cannot retain their chirality after dissolution ( Figure S18, Supporting Information), that is, the induced predominated one-handed helixes can be maintained only in nanoparticle state. We think the cause of this phenomenon may be due to the thermodynamic control in the HSSDP process.…”
Section: Introductionmentioning
confidence: 99%
“…Apart from the CPPs constructed by pure racemic helical polymers, Deng's group prepared CPPs/GO hybrid nanocomposites by helix-sense-selective co-precipitations (HSSCP) of chirally modified GO and racemic helical polymers in THF/ water solution systems. [55] The chirally modified GO acted as a chiral source for inducing and further stabilizing the predominantly induced one-handed helicity in the optically inactive helical polymers. Three racemic helical polymers underwent HSSCP along with chirally modified GO resulting in CPPs/ GO hybrid materials.…”
Section: Cpps Constructed By Racemic Helical Polymersmentioning
confidence: 99%
“…Optically active helical polymers have attracted great attention owing to their fascinating helical structures and significant potentials in chiral recognition, chiral separation, and asymmetric catalysis . Optically active spheres combining the advantages of helical polymers and the strength of particulate materials become increasingly interesting as a newly emerging type of advanced materials . More importantly, spheres with remarkable optical activity are expected to be prepared from chirally helical polymers holding “chiral amplification” effects .…”
Section: Introductionmentioning
confidence: 99%
“…[20] Optically active spheres combining the advantages of helical polymers and the strength of particulate materials become increasingly interesting as a newly emerging type of advanced materials. [21][22][23][24] More importantly, spheres with remarkable optical activity are expected to be prepared from chirally helical polymers holding "chiral amplification" effects. [25,26] In our earlier studies, we have prepared optically active polymeric spheres constructed by chirally helical substituted polyacetylenes by diverse polymerization methods.…”
mentioning
confidence: 99%